2011
DOI: 10.1007/s00467-011-2034-3
|View full text |Cite
|
Sign up to set email alerts
|

Glucose intolerance: is it a risk factor for cardiovascular disease in children with chronic kidney disease?

Abstract: A total of 66 children and adolescents with chronic kidney disease (CKD) (20 pre-dialysis patients and 46 chronic dialysis patients) were evaluated to address the prevalence of abnormalities in glucose and insulin metabolism and their association with cardiovascular disease. Glucose intolerance was assessed using an oral glucose tolerance test; insulin resistance was estimated by the homeostasis model assessment of insulin resistance (HOMA-IR). Carotid artery intima-media thickness (IMT) and left ventricular h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 50 publications
2
5
0
5
Order By: Relevance
“…Another finding was the association between serum hemoglobin and LVM, which is consistent with data from the literature that reports an association between anemia and LVMI 22,30. In a cross-sectional study evaluating 156 children undergoing dialysis with similar mean age to that of our study, an independent association between low serum hemoglobin and LVMI was reported 22.…”
Section: Discussionsupporting
confidence: 91%
“…Another finding was the association between serum hemoglobin and LVM, which is consistent with data from the literature that reports an association between anemia and LVMI 22,30. In a cross-sectional study evaluating 156 children undergoing dialysis with similar mean age to that of our study, an independent association between low serum hemoglobin and LVMI was reported 22.…”
Section: Discussionsupporting
confidence: 91%
“…IFG and IGT are common in pediatric CKD, including dialysis patients. Using the ADA definitions, 35% of pediatric non-dialysis CKD patients exhibit either IFG or IGT ( 35 ). While the prevalence for hyperinsulinemia varies between studies of pediatric CKD stage 2–4 (9–33%), insulin resistance reveals similar prevalence (16–19%) ( 36 ).…”
Section: Risk Factors and Risk Markersmentioning
confidence: 99%
“…Disorder of the glucose and insulin metabolism in children with CKD on therapy with HD, and especially after kidney transplant is becoming more frequent 5 . Small studies on children with CKD, stage 2-4 or on HD, show that the prevalence of hyperinsulinemia is 33% and the prevalence of insulin resistance disorder is up to 16% (measured by homeostasis model assessment-estimated insulin resistance -HOMA IR) 33,34 . It appears that abnormalities in glucose and insulin metabolism are more prevalent than they were deemed to be.…”
Section: Disorders Of Glucose and Insulin Metabolismmentioning
confidence: 99%
“…It appears that abnormalities in glucose and insulin metabolism are more prevalent than they were deemed to be. Recent publications featuring studies on children after kidney transplantation have shown that the frequency of disorders of glucose and insulin metabolism is from 16% to 18% 33,35 .…”
Section: Disorders Of Glucose and Insulin Metabolismmentioning
confidence: 99%